Arthrostoma supriatnai sp. nov. (Nematoda: Ancylostomatidae) parasitic in Mydaus javanensis (Carnivora: Mephitidae) from Mount Ciremai, Java, Indonesia - Dewi, Kartika; Purwaningsih, Endang; Hasegawa, Hideo (Zootaxa, 2023)
Arthrostoma supriatnai sp. nov. was described from Mydaus javanensis obtained from Mount Ciremai, Java, Indonesia. It is characterized by having a buccal capsule with ten articulated plates including a pair of additional lateral plates. To date, the genus Arthrostoma consists of eleven species that are native to Asia. Of them, only A. miyazankiense and A. tunkanati have ten articulated plates including the lateral plates. However, the present species has a much stouter body, being readily distinguishable from these two species. Moreover, its male has much shorter spicules than A. miyazakiense, and an arrow-shaped gubernaculum, differing from A. tunkanati, in which gubernaculum is distally bifid. In the female, the present species is readily distinguished from these two species in the shape and number of vulval swellings.